Medical jousting: ethical and legal considerations - Devendra Jadav; Sathish Ayyappan; Vikas P. Meshram; Tanuj Kanchan (International Journal Of Community Medicine And Public Health, 2026)
Medical jousting refers to making insulting or disparaging remarks about a fellow medical practitioner, usually in front of the patient or next of kin of the patient. These comments can be made intentionally or unintentionally. The results can be stressful for the patient and the medical professionals involved. Medical jousting produces various ethical and legal issues. To reduce instances of medical jousting, regulatory bodies of the medical profession should declare the act of jousting unethical and punishable with disciplinary action. Medical practitioners should think rationally before criticizing another medical practitioner and communicate with them directly to avoid any conflict.